XVI. yüzyıl şairi Ahdî-i Bağdadi Divanı - Bedestani, Ayşe (My University, 2018)
Bu çalışmada, çeşitli mecmualarda şiirleri olan, ancak mürettep bir divanı bulunmayan XVI. yüzyıl şairi ve tezkire yazarı Ahdî-i Bağdâdî’nin şiirlerinin toplanıp şairin Dîvân metninin ortaya çıkarılması amaçlanmıştır.Çalışma, iki bölümden oluşmaktadır. Birinci bölümde Ahdî-i Bağdâdî’nin Hayatı ve Edebi Kişiliği ele alınmış, ikinci bölümde ise 292 şiirden oluşan Divan metni ortaya konmuştur.

In this study, it’s aimed to uncover the Divan, which was published some magazines but not collected so far, is belong to Ahdi, the 16th century poet and book writer.The study consists of two chapters. In the first chapter, the life and literary personality of Ahdi was reviewed and in the second chapter 292 poetry texts arranged.
Keywords: Ahdî; Divan; History and criticism; magazine; mecmua; poem; şiir Ahdi; Tarih ve eleştiri; Turkish poetry; Türk şiiri